Análisis socioeconómico de los inmigrantes venezolanos en la Ciudadela Sauces de la ciudad de Guayaquil, Ecuador - Clavijo Campozano, David Leonardo (2022)
The main objective of this research is to analyze the socioeconomic situation of Venezuelan immigrants in the Sauces neighborhood in the city of Guayaquil. The immigration of Venezuelans to Ecuadorian soil is a social phenomenon that began when the political, economic and social situation in Venezuela was at its worst. Arriving in Ecuador has not been easy for them, many have had to choose the dangerous path of the "trochas". The research is developed in the Sauces neighborhood in the city of Guayaquil, a place where there is a regular settlement of a very significant population of Venezuelan immigrants. According to the documentary research carried out, the city of Guayaquil is the preferred place to settle, due to its wide commercial activity. The results of this research were obtained through a mixed approach, the scope is documentary and descriptive. Observation and survey were used for data collection. The survey was conducted with 46 Venezuelans. The results of the surveys show that the socioeconomic situation of Venezuelan immigrants is not precarious; however, there is much room for improvement. It was corroborated that most of them are unregistered migrants, live informally, have low incomes and are not affiliated with social security. Based on the conclusions, it was found that a considerable number arrived by land transport, there are laws that protect immigrants and actions should be formulated to further improve the living conditions of Venezuelan immigrants.